2014
DOI: 10.1186/s40200-014-0113-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of family support improvement behaviors on anti diabetic medication adherence and cognition in type 2 diabetic patients

Abstract: BackgroundGlycaemic control is the main goal of treatment for type 2 diabetic patients. Hyperglycaemia may result in cognitive decline. More family support may increase medication adherence and decrease glycaemic level. The purpose of this study was to determine the impact of family support improvement behavior on anti diabetic medication adherence and cognition in type 2 diabetic patients.MethodThe randomized control trial study was conducted on 91 patients from an outpatient diabetes clinic. They were random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 37 publications
2
43
0
1
Order By: Relevance
“…This review verified that five studies follow-up the program by using a face-to-face follow-up (12,15,17,(22)(23)(24)33) . Three studies were noticed to follow-up the program by using the telephone method (13,14,25,26,32) .…”
Section: Follow-up Strategiesmentioning
confidence: 91%
See 4 more Smart Citations
“…This review verified that five studies follow-up the program by using a face-to-face follow-up (12,15,17,(22)(23)(24)33) . Three studies were noticed to follow-up the program by using the telephone method (13,14,25,26,32) .…”
Section: Follow-up Strategiesmentioning
confidence: 91%
“…We found that DSME based individual program was conducted into 40.9% of the studies (12,13,16,20,23,25,29,30,32) and 59.1% of the studies offered the DSME in a combination of individual and group education (12,14,15,17,20,21,27,31,32,34) . In general, The individual or group-based program provided the intervention of several strategies, including personalized counseling, feedback regarding goal-setting and problem-solving, support for self-care practice from family members, and the follow-up session.…”
Section: Diabetes Mellitus Self-management Education (Dsme)mentioning
confidence: 99%
See 3 more Smart Citations